Leaf Extracts of Anchomanes difformis Ameliorated Kidney and Pancreatic Damage in Type 2 Diabetes - Toyin Dorcas Alabi; Nicole L. Brooks; Oluwafemi O Oguntibeju (Plants, 2021)
Kidney disease in diabetes is one of the common microvascular complications of diabetes mellitus implicated in end-stage renal failure. This study explored the ability of Anchomanes difformis to ameliorate kidney and pancreatic damage in type 2 diabetes mellitus using male Wistar rats. Two weeks of fructose (10%) administration followed by streptozotocin (40 mg/kg) were used to induce type 2 diabetes. Leaf extract (aqueous) of Anchomanes difformis (200 mg and 400 mg/kgBW) was administered orally for six weeks. Body weights were monitored, urea and creatinine were measured. Interleukins (IL)-1β, IL-6, IL-10, IL-18, and TNFα were measured in the kidney lysate. CAT, SOD, ORAC, FRAP, and MDA levels were also evaluated in the kidney. Transcription factors (Nrf2 and NF-ĸB/p65) and apoptotic markers (Bcl2 and caspase 3) were investigated in the kidney. Histological sections of the pancreas and kidney tissues were examined for any visible pathology. Supplementation with Anchomanesdifformis enhanced antioxidant status, modulated inflammatory response, and reduced apoptosis in the kidney. It also restored the kidney and pancreatic histoarchitecture of the treated diabetic rats. The pathophysiology associated with diabetic nephropathy and pancreatic damage showcase the importance of exploring the use of antidiabetic, nephroprotective agents such as Anchomanes difformis to kidney damage in type 2 diabetes.